Cysteine Oxidations in Mitochondrial Membrane Proteins: The Case of VDAC Isoforms in Mammals - Reina, Simona; Pittalà, Maria Gaetana Giovanna; Guarino, Francesca; Messina, Angela; De Pinto, Vito; Foti, Salvatore; Saletti, Rosaria (Frontiers in Cell and Developmental Biology, 2020)
Cysteine residues are reactive amino acids that can undergo several modifications driven by redox reagents. Mitochondria are the source of an abundant production of radical species and it is surprising that such a large availability of highly reactive chemicals is compatible with viable and active organelles, needed for the cell functions. In this work we review the results highlighting the modifications of cysteines in the most abundant proteins of the outer mitochondrial membrane, i.e. the VDAC isoforms. This interesting protein family carry several cysteines exposed to the oxidative intermembrane space. Thorough mass spectrometry analysis cysteine PTMs were precisely determined and it was discovered that such cysteines can be subject to several oxidization degrees, ranging from the disulfide bridge to the most oxidized, the sulfonic acid, one. The large spectra of VDAC cysteine oxidations, which is unique for OMM proteins, indicate that they have both a regulative function and a buffering capacity able to counteract excess of mitochondria ROS load. The consequence of these peculiar cysteine PTMs are discussed.